Menjaga Integritas Bisnis Etika Pemasaran Syariah di Era Modern - Abroza, Ahmad; Wardani, Ratih Ajeng Kusuma; Kadir, Abdul; Ismail, Muhammad; Megantoro, Ardi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze the implementation of ethical marketing in Islamic marketing and its impact on business integrity in modern companies. The background of this research is driven by the importance of understanding ethical values in marketing based on Islamic principles, especially in the era of increasingly competitive market competition. The research method used is a qualitative approach, including in-depth interviews, observations, and document analysis in several companies that apply ethical marketing in Islamic marketing. The findings show that the implementation of principles such as honesty, transparency, and fairness can enhance consumer trust and strengthen customer loyalty. However, challenges still exist, particularly regarding consistent understanding across the organization and pressure for short-term profits. The implications of this study emphasize the importance of intensive training for employees on Islamic marketing ethics and the development of value-based marketing approaches to improve company reputation and sustainability.